Analisis Strategi Wisata Tirta Agung Dalam Upaya Pengembangan Pariwisata Di Kabupaten Bondowoso - Nahdiyah Farohidal Hidayati; Mohammad Rizal; Sulton Sholehuddin (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Tirta Agung Tourism is a tourist destination located in Sokleh Timur Hamlet, Sukosari Kidul Village, Sumber Wringin District, Bondowoso Regency. One of the tourist destinations that needs to be developed so that it continues to operate and innovate. In developing Tirta Agung tourism requires a strategy in determining the direction of its destination. The purpose of this research is to analyze Tirta Agung's tourism development strategy. As well as being able to identify potential resources for the development of Tirta Agung tourism.The type of research used in this research is qualitative with data collection methods using observation, documentation, interviews. For the method of analysis researchers use SWOT analysis. The results of this study indicate that the internal factor (IFAS) is greater than the external factor (EFAS) for Tirta Agung tourism, which means that the strategic position of Wista Tirta Agung is at the SO (Strenght-Opportunity) coordinate point. Then the strategy that can be applied in developing Tirta Agung Tourism is an aggressive growth strategy or growth strategy. Keywords: Tirta Agung Tourism, Tourism Development, Strategy Analysis